Business Fight of Indonesian E-Commerce Platforms and Its Impact on Consumer Behavior of Tokopedia, Lazada and Shopee Indonesia Platforms - Fandiyanto, Randika; Ediyanto; Rachman, Riza; Sari, Rini Kartika; Faiza, Nur; Widiarti, Dian; Syahputra, Hendra (International Journal of Social Science and Business, 2025)
The development of e-commerce in Indonesia has changed the lifestyle of Indonesian people. Consumers prefer online transactions over conventional transactions, because online transactions can be done quickly and easily without being hindered by space and time. This study examines the causal relationship between exogenous variables (Seller Price Policy, SEPAd, Live Commerce, Service Delivery, Product Review) through intervening variables (Online Trust, Purchase Decision, Customer Satisfaction) on the endogenous variable (Loyalty). Respondents in this study were 185 consumers of fashion products on the e-commerce platforms Bukalapak, Shopee, Tokopedia. The data analysis tool used was Structural equation modelling (SEM). The results of the first research hypothesis test showed that Seller Price Policy had a significant positive effect on Online Trust, while for SEPAd, Live Commerce, and Delivery Service had a significant positive effect on Online Trust. Meanwhile, Review of Product had a positive but insignificant effect on Online Trust. The results of the second hypothesis test show that Seller Price Policy, SEPAd, Live Commerce, Service Delivery and Review of Product have a positive but insignificant influence on Purchase Decisions. The third hypothesis found that Online Trust has a significant positive influence on Purchase Decision. The fourth hypothesis test results found that Online Trust has a positive but insignificant influence on Customer Satisfaction. The fifth hypothesis test results found that Purchase Decision has a significant positive influence on Customer Satisfaction. The sixth hypothesis test results found that Purchase Decision has a positive but insignificant influence on Loyalty. The seventh hypothesis test results found that Customer Satisfaction has a significant positive influence on Loyalty. The indirect test results show that Seller Price Policy, SEPAd, and Direct Trading have a positive and significant influence on Loyalty through Online Trust, SEPAd, and Customer Satisfaction. Meanwhile, Service Delivery and Product Reviews have a negative but insignificant effect on Loyalty through Online Trust, SEPAd, and Customer Satisfaction.